Implementing cleaner heating solutions towards a future low-carbon scenario in Ireland. (20th March 2019) - Thellufsen, Jakob Zinck; Nielsen, Steffen; Lund, Henrik
Abstract: Studies show that energy efficiency should play a significant role towards achieving cost-efficient 100% renewable energy systems. One way to attain cleaner heating solutions for the future is to utilise waste heat from power plants and industry through district heating. In the European Union, approximately 50% of thermal energy is lost in conversion processes. This research paper investigates the potential for the implementation of district heating in a future energy system originally intended not to include district heating. The paper approaches the problem by utilising TIMES modelling to frame the initial future energy system. However, MARKAL/TIMES is not ideal to investigate the operation of different heating scenarios, due to a lack of hourly modelling. Hence, the study utilises EnergyPLAN to investigate the implementation of district heating as an alternative heating scenario to individual heating. EnergyPLAN allows for simulating the hourly operation of not only electricity systems but also heating systems. The study investigates the implementation of district heating in the CO2-80 scenario created with the Irish TIMES model. As the Irish CO2-80 scenario does not include district heating, this study uses EnergyPLAN to simulate an 80% reduction scenario, with and without district heating, to compare the operation of the two systems. A sensitivity analysis is included to reflect on the uncertainties of the study. The results show that a district heating solution is more fuel-efficient while more investment heavy, however the fuel savings more than compensates for the increased investments. In total, the district heating scenario is close to 300 M € cheaper in annual costs than the individual heating scenario for Ireland, and achieves a fuel efficiency increase of 3.5% in the whole energy system due to an efficiency increase in the heating sector. The article shows both the relevance of using multiple models, and the need to consider district heating in a future Irish energy system. Highlights: EnergyPLAN is capable of simulating energy systems identified in MARKAL/TIMES. EnergyPLAN and Markal/TIMES combined enables better analysis of heating scenarios. District heating can compete with individual heating in an Irish energy system.